Association of nitrite inhalants use and unprotected anal intercourse and HIV/syphilis infection among MSM in China: a systematic review and meta-analysis - Zhang, Yonghui (BMC Public Health, 2020)
BACKGROUND: Nitrite inhalant use is very common among men who have sex with men (MSM) in China. However, there is lack of national representative data on use among Chinese MSM, and the mechanism of how nitrite inhalant use impacts HIV infection in MSM is unclear. This meta-analysis aims to understand the characteristics of Chinese MSM nitrite inhalant users and to determine the associations between nitrite inhalant use and sexual behaviors, the prevalence of HIV, and the prevalence of syphilis. METHODS: We searched PubMed, Web of Science, Chinese National Knowledge Infrastructure, Chinese Wanfang Data, and VIP Chinese Journal Database for relevant literature published from January 1985 to December 2017. RESULTS: Fifteen eligible studies, with a total of 18,981 Chinese MSM participants, were included. Compared with nitrite inhalant nonusers, users were more likely to be younger, have a higher level of education, and seek sexual partners using the Internet. Nitrite inhalant users were more likely to engage in high-risk sexual behaviors, including condomless anal intercourse (odds ratio [OR] = 1.33), group sex (OR = 2.26), and commercial intercourse (OR = 1.50). Nitrite inhalants users had a higher prevalence of HIV (OR = 1.83), higher prevalence of syphilis (OR = 1.38) and had higher lifetime HIV testing rates (OR = 1.33) compared with nonusers (each p < 0.05). CONCLUSIONS: Nitrite inhalant users have higher HIV and syphilis prevalence by increasing levels of high-risk sexual behaviors. China should expand HIV testing, treatment as prevention (TasP), and Pre-exposure prophylaxis (PrEP) among MSM, especially among nitrite inhalants using MSM, to reduce their risk of HIV infection and transmission.